Ultra‐Stable Phase Change Coatings by Self‐Cross‐Linkable Reactive Poly(ethylene glycol) and MWCNTs. (25th November 2021) - Cui, Junshuo; Li, Wenkang; Wang, Yuejiao; Yu, Haibiao; Feng, Xiaogeng; Lou, Zhenning; Shan, Weijun; Xiong, Ying
Abstract: Form‐stable phase change materials (PCMs) have great potential to regulate the unbalanced heat demand and supply, yet most of the PCMs are in powder, plate, or bulk rigid forms, difficult to adhere to the heat source or target substrates. Herein, PCMs coatings based on reactive poly(ethylene glycol) (RPEG) are developed for direct thermal energy exchange and storage. RPEG with highly reactive silanol groups is obtained by reaction of PEG with 3‐isocyanatopropyltriethoxysilane (IPTS), followed by hydrolyzation in weak acid. Cross‐linked PCMs coatings are obtained on various substrates, including cotton fabric, wood, tinplate, and even irregular objects. The coatings show obvious solid‐solid phase transition properties and high energy storage densities (142.8 J g −1 ). Multi‐walled carbon nanotubes (MWCNTs) are further doped into the coatings aided by a self‐cross‐linkable dispersant. The composite coatings exhibit excellent high‐temperature form stability and rapid thermal exchange properties owing to the formation of the cross‐linked network between RPEG and MWCNTs. Thermal regulation clothes are prepared by a spray coating method, which show no performance deterioration after washing three times, indicating good washing durability. Abstract : Self‐cross‐linkable poly(ethylene glycols) are synthesized and used for constructing phase‐change coatings for direct thermal energy storage. The coatings are suitable for wood, iron, cotton substrate, and show obvious solid–solid phase change behavior, high energy storage density, and excellent form stability. The mechanical strength and thermal conductivity are further enhanced by homogeneously doping with multi‐walled carbon nanotubes aided by a reactive dispersant.